(untitled) (Asian Journal of Medical Research and Health Sciences, 2023)
Mothers gift not just life but also a microbial profile to their babies, i.e., for vaginally delivered babies, these commu-nities resemble the specific microbial communities found in the mother’s birth canal; for babies delivered by caesare-an section, the communities resemble the skin communities of the mother. These gut microbiota, via a complex bidi-rectional communication system, interact with the Central Nervous System, the enteric nervous system, and the hypo-thalamo-pituitary-adrenal axis (HPA) (cognitive and emotional centers), referred to as the Gut-Brain axis. Though in contemporary societies microbes have a strong negative connotation and are viewed in a warlike context, not all are harmful but beneficial and indeed crucial for a normal healthy life. As many ongoing research studies link the patho-genesis of various diseases to altered gut microbiota, many studies on the other hand show dramatic recovery with faecal microbiota transplantation, confirming the earlier